The Role of Rumination as a Mediator of Psychological Distress Relationships and Nonsuicidal Self-Injury Behavior in Adolescent Victims of Bullying - Andi Khairunnisa Putri; Monty P. Satiadarma; Roswiyani Roswiyani (Journal La Sociale, 2024)
Nonsuicidal self-injury (NSSI) is the deliberate destruction of body tissue without suicidal intent. NSSI occurs a lot in adolescents. Bullying is the most common factor in adolescents who commit NSSI. The impact of other than NSSI on adolescent bullying victims is psychological distress. Previous research stated that psychological distress can cause NSSI behavior needs to be mediated by a variable, one of the variables that can be related is rumination. This study aims to determine the role of rumination as a mediator of the relationship between psychological distress and NSSI behavior in adolescent bullying victims. The study design is non-experimental. Participants were adolescents aged 16–21 years, experienced bullying, self-harm within 12 months (n=60). The sampling technique used is non probability sampling. The instrument of this study was K10 for psychological distress (α=.86). Ruminative Response Scale (RRS) for rumination (α=.75) and Inventory of Statement About Self Injury (ISAS) for NSSI behavior (α=.83). Results showed that rumination does not mediate the relationship of distress and NSSI in adolescent victims of bullying. However, psychological distress correlated and have a role in the emerge of rumination and NSSI in adolescent bullying victims. ANNOVA test showed that distress, rumination and NNSI were highest in participants with a high frequency of bullying. Therefore, it is important to intervene reduce psychological distress in adolescents and take preventive action and education related to the impact of bullying.